2014
DOI: 10.1007/s10517-014-2637-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mitochondrial Fluorescent Dyes in Stromal Cells

Abstract: Specific fluorescent mitochondrial dyes JC-1, MitoTracker Red FM, and MitoTracker Red CMXRos were studied on cultures of mesenchymal stromal stem cells from human adipose tissue. Static and dynamic experiments demonstrated the dependence of dye accumulation in the mitochondria and cytoplasm on mitochondrial potential in the presence of oxidative phosphorylation uncoupler CCCP. JC-1 dye demonstrated most pronounced bleaching upon repeated laser exposure even in very low doses, which should be taken into account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Interestingly, GC7 never induced a total breakdown of DC m , which was classically observed in cells entering apoptosis (total DC m dissipation is ,3% of the GC7-treated cells only; area M1) ( Figure 2C). We obtained the same effect by measuring directly the fluorescence of the mitochondrial potential probe Mitotracker red FM 18 on intact confluent epithelia (Supplemental Figure 4). Interestingly, this GC7-induced decrease in DC m was not related to an upregulation of the uncoupling proteins UCP2 (Supplemental Figure 3B) or UCP3 (Supplemental Figure 3C).…”
Section: Inhibition Of Eif5a Hypusination Induces Metabolicmentioning
confidence: 84%
“…Interestingly, GC7 never induced a total breakdown of DC m , which was classically observed in cells entering apoptosis (total DC m dissipation is ,3% of the GC7-treated cells only; area M1) ( Figure 2C). We obtained the same effect by measuring directly the fluorescence of the mitochondrial potential probe Mitotracker red FM 18 on intact confluent epithelia (Supplemental Figure 4). Interestingly, this GC7-induced decrease in DC m was not related to an upregulation of the uncoupling proteins UCP2 (Supplemental Figure 3B) or UCP3 (Supplemental Figure 3C).…”
Section: Inhibition Of Eif5a Hypusination Induces Metabolicmentioning
confidence: 84%
“…To assess localization, we compared the intracellular fluorescent emission of 2 and 3 to that of MitoTracker Red CMXRos (MTR), which is known to localize in the mitochondria . Incubation of A549 cells with 2 at 100 μM for 4 h showed that the compound localizes similarly to the MTR dye as indicated by the yellow-orange color in the merged image (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the dye's covalent binding to sulphhydryl groups, it may only tentatively be considered as potential sensitive mitochondrial dye, and we cannot discern whether the activity or the number of mitochondria amplified after IVM. Furthermore, it needs to be mentioned that Buravkov et al (2014) also demonstrated that the dye with the advantage to be stable after fixation not only binds sulphhydryl groups in mitochondria, but also in the cytoplasm of cells. Interestingly, it is reported that the content of free cytoplasmic sulphhydryl groups, particularly of glutathione, increases upon oocyte maturation in different species which is dependent on the presence of cumulus cells and precursor molecules (bovine: de Matos, Furnus, & Moses, 1997; horse: Luciano, Goudet, Perazzoli, Lahuec, & Gérard, 2006).…”
Section: Freitasmentioning
confidence: 99%
“…Because of the negative membrane potential, mitochondria accumulate lipophilic cations and several fluorescent probes have been developed to monitor mitochondrial function in living cells (Buravkov, Pogodina, & Buravkova, 2014;Cottet-Rousselle, Ronot, Leverve, & Mayol, 2011;Johnson, Walsh, Bockus, & Chen, 1981;Niżański, Partyka, & Rijsselaere, 2012;Smiley et al, 1991). However, fluorescence emitted by these conventional mitochondrial markers is often susceptible to photobleaching during microscopic examination and the marker exhibit photoinduced toxicity (Chen, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation